Ultrafast Raman fiber Laser with Random Distributed Feedback. Issue 4 (12th March 2018) - Pan, Weiwei; Zhang, Lei; Jiang, Huawei; Yang, Xuezong; Cui, Shuzhen; Feng, Yan
Abstract: Ultrafast Raman fiber lasers are wavelength‐agile light sources for various scientific and medical applications. Pulse pumping is an efficient way to generate a high power ultrafast Raman fiber laser, which however requires real‐time synchronization between the pump pulses and laser cavity. A pulse pumped Raman fiber laser with random distributed feedback is investigated. Under repetitive pulse pumping, compound cavities based on distributed Rayleigh scattering are formed automatically to synchronize with the pump pulse train. In a proof of principle experiment, self‐synchronization is observed and a stable picosecond pulsed random laser is generated at 1120 nm with an average power of 170 mW. Raman gain and random distributed feedback are spatially separated in the present pulse pumped laser configuration. This allows a direct characterization of the random distributed feedback and a comparison between random lasing and amplified spontaneous emission, which is not possible in previous continuous wave pumped random Raman fiber lasers. Abstract : A pulse pumped Raman fiber laser with random distributed feedback is investigated. Under repetitive pulse pumping, compound cavities based on distributed Rayleigh scattering are formed automatically to synchronize with the pump pulse train. The self‐synchronization mechanism offers a novel method to generate wavelength‐agile ultrafast Raman fiber lasers.